'I can do this': a qualitative exploration of acceptability and experiences of a physical activity behaviour change intervention in people with multiple sclerosis in the UK. Issue 3 (6th March 2020) - Fortune, Jennifer; Norris, Meriel; Stennett, Andrea; Kilbride, Cherry; Lavelle, Grace; Hendrie, Wendy; de Souza, Lorraine; Abdul, Mohamed; Brewin, Debbie; David, Lee; Anokye, Nana; Victor, Christina; et al.
Abstract : Objectives: The purpose of this study was to explore the experiences of people with multiple sclerosis (MS) who participated in iStep-MS, a feasibility randomised controlled trial of a behaviour change intervention that aimed to increase physical activity and reduce sedentary behaviour. Design: A qualitative approach was undertaken embedded in the feasibility randomised controlled trial. One-to-one semi-structured interviews were conducted and analysed using Framework analysis. Setting: Participants were recruited from a single MS therapy centre in the southeast of England, UK. Participants: Sixty people with MS were randomly allocated in a 1:1 ratio to the intervention or usual care. Following a purposive sampling strategy, 15 participants from the intervention arm undertook 1:1 semi-structured interviews. Interventions: The iStep-MS intervention consisted of four therapist-led sessions over 12 weeks, supported by a handbook and pedometer. Results: Three themes were identified from the data. "I can do this": developing competence in physical activity highlights the enhanced physical activity confidence gained through goal setting and accomplishment. " I felt valued": the nurturing culture provides an overview of the supportive and non-judgemental environment created by the programme structure and therapeutic relationship. Finally, " What can I do?": empowered enactment describes the transition from the supported iStep-MS intervention to intrinsically motivated physical activity enactment. Conclusions: Overall, this study supports the acceptability of the iStep-MS intervention and identified key areas that supported participants to be physically active. Trial registration number: ISRCTN15343862 .